The Strategies of Enhancing Zakat Education in Indonesia - Santo Hartono, Haryani (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2023)
Starting zakat education needs to be pursued as early as possible, continuing at the stages of youth and adulthood, and applying it in old age. Implementing the strategies in zakat education is a long journey. This study describes the strategy used by the National Zakat Board (BAZNAS), as the only Indonesia government zakat agency in improving zakat education in Indonesia. This study uses a descriptive qualitative approach, describing the stages in implementing zakat education. BAZNAS in carrying out its role collaborates with the experts in education to further increase zakat literacy in society. The strategy in educating the public about zakat requires support from all parties, be it the government, educational institutions, and the community itself.